Development of Acoustic and Thermal Insulation Materials from Pantyhose Waste - Kucukali-Ozturk, M.; Sezgin, H.; Yalcin-Enis, I.; Dolu, C. (Trans Tech Publications Ltd, 2023)
Population growth, urbanization, industrialization, developing technology, increasing welfare level and changing consumption habits cause solid wastes to increase day by day. There are also sub-waste groups that have not yet been fully recognized among the solid waste groups in which textile wastes have a large share. One of them is pantyhose, which has been indispensable for modern life since the day it was presented to the consumer. These socks, which are made of polyamide and elastane fibers that are easily punctured, run and become unusable when worn once or several times, are generally thrown away after use. These pantyhose wastes, which are not biodegradable due to their raw materials, also pose an environmental risk. Within the scope of the study, thermal and sound insulation properties of carded and needle-punched pantyhose wastes are investigated. The results show that the thermal and acoustic properties of the developed material are at a sufficient level, and it has ensured that polyamide wastes, which have superior properties among thermoplastic polymers and have high economic value, are brought back into the economy. © 2023 Trans Tech Publications Ltd, Switzerland.
Keywords: Pantyhose; Recycling; Sound Insulation; Textile Waste; Thermal Insulation